Connected drug delivery devices to complement drug treatments: potential to facilitate disease management in home setting - Bittner B (Dove Medical Press, 2019)
Beate Bittner,1 Chantal Schmit Chiesi,1 Saifuddin Kharawala,2 Gavneet Kaur,2 Johannes Schmidt1 1Product Optimization, Global Product Strategy, F. Hoffmann-La Roche Ltd, 4070 Basel, Switzerland; 2Bridge Medical Consulting Ltd, Richmond, London, TW9 2SS, UK Abstract: Connected drug delivery devices are increasingly being developed to support patient supervision and counseling in home setting. Features may include dosing reminders, adherence trackers, tools for patient education, and patient diaries to collect patient-reported outcomes, as well as monitoring tools with interfaces between patients and health care professionals (HCPs). Five connected devices have been selected as the basis for a review of the clinical evidence concerning the impact of electronic tools on treatment adherence and efficacy outcomes. Disease areas covered include multiple sclerosis, diabetes, hypertension, liver and renal transplant recipients, tuberculosis, hepatitis C, clinically isolated syndrome, asthma, and COPD. From studies comparing the use of electronic feedback tools to standard of care, there is an initial evidence for a higher adherence to treatment and better outcomes among patients who use the electronic tools. To substantiate the assumption that connected devices can improve adherence in an outpatient setting over a prolonged period of time, further data from controlled randomized studies are required. Key barriers to the broader adoption of connected devices include data privacy laws that may prevent data sharing with HCPs in some countries, as well as the need to demonstrate that the tools are consistently used and generate a high-quality and reproducible database. If these challenges can be addressed in a way that is agreeable to all stakeholders, it is expected that the future value of connected devices will be to 1) facilitate and improve patient involvement in disease management in a flexible care setting, 2) enable early treatment decisions, and 3) complement value-based reimbursement models. Keywords: home-administration, self-administration, connected drug delivery device, adherence, patient-reported outcomes, real-world evidence